Examining the implementation of disaster risk reduction education for students with visual impairments - Ike Fitri Samsiyah; Chatarina Muryani; Singgih Prihadi (Journal of Environment and Sustainability Education, 2026)
Disaster Risk Reduction (DRR) education is an important component in building school resilience, especially for students with disabilities who are more vulnerable in disaster situations. The purpose of this study is to analyze the implementation, inclusivity, and accessibility of DRR education for visually impaired students within the framework of SPAB in Kulon Progo Regency. This study employs a qualitative approach, with data collected through in-depth interviews, observations, and document analysis based on the SPAB Pillar 3 framework. The research involved school principals, teachers, and school staff from three special schools: State Special School 1 of Kulon Progo, Bhakti Wiyata Special School, and Zafa Hargorejo Special School. The findings show that DRR education for students with visual impairments in Kulon Progo Regency has been implemented quite well with the integration of education into learning, extracurricular, and disaster simulation activities in collaboration with related institutions. However, the level of inclusivity in its implementation is still not optimal and is largely influenced by the limited learning resources that are accessible for visually impaired students. This study underscores the need to strengthen inclusive DRR educational practices to ensure that students with visual impairments have equitable access to knowledge, skills, and disaster resilience development through collaboration among school communities and relevant stakeholders. This research has several limitations, so future research is expected to be conducted within a wider scope and research focus.